Development of a Web-Based Illustrated Acehnese - Indonesian Dictionary for Primary Education: Pengembangan Kamus Aceh-Indonesia Berilustrasi Berbasis Web untuk Pendidikan Dasar - Rahil Helmi; Dinda Destari; Inas Ghina; Melda Munawwarah (Language Development Center, 2025)
Background: The use of the Acehnese language among young generations has significantly declined in recent years, particularly at the primary school level. One of the main contributing factors is the lack of engaging, interactive, and contextually relevant learning resources for teaching the Acehnese language. Purpose: This study aims to design and develop a web-based illustrated Acehnese–Indonesian dictionary as an innovative learning resource to support Acehnese language learning in primary schools. The dictionary is designed to be child-friendly, culturally contextual, and accessible through various digital devices, and is expected to address the scarcity of Acehnese language learning media that teachers have long faced. Method: This research employed a Research and Development (R&D) approach using the 4D model (define, design, development, disseminate). Data were collected through observations, interviews, and questionnaires involving 6 primary school teachers, 3 Acehnese language experts, 3 information technology experts, and 30 students as end users. The data were analysed using qualitative descriptive methods to examine the content and technical feasibility, and quantitative descriptive methods to assess user responses towards the developed dictionary prototype. Results and Discussion: The results indicate that the web-based illustrated Acehnese-Indonesian dictionary is feasible for use as a learning medium for the Acehnese language in primary schools. Validation by language experts received an average score of 89%, IT experts 83%, limited trials with students 92%, and teachers 94%. Conclusions and Implications: These findings suggest that the developed dictionary is effective, user-friendly, and has strong potential to support the revitalisation of the Acehnese language through formal learning in primary schools. The developed dictionary is feasible and recommended for classroom use, yet requires continuous content updates and training for teachers.